Gender, Religion, and Indefinability in La burladora de Toledo - Lindstrom, Naomi (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2023)
The 2008 novel La burladora de Toledo by Angelina Muñiz-Huberman is the fictional recreation of the wandering life of an individual who lived in sixteenth-century Spain as, at various times, a man and as a woman. The novel at first appears to have two themes: the main character’s unrecognizable gender and their highly syncretistic and extraofficial religious life. My thesis is that in La burladora gender and religion, which initially manifest as two concerns, are facets of a broader concept that the narrative promotes. Burladora assigns a positive value to identities that are fluid, mutable, and indefinable.